(untitled) (Mustansiria Dental Journal, 2025)
Aim of the study: to evaluate the effect of probiotics on gingival health and levels of IL-6 in saliva. Measuring levels of IL-6 in different intervals at zero time before taking probiotic lozenges, 14 days after daily intake of probiotics, and after 28 days of daily intake of probiotics with measuring the gingival index (GI) for children. Material and method: A prospective study was conducted from 18, November 2023 to 18, December 2023, involving 100 children (49 females and 51 males) aged 10 years in Anbar, Iraq. Saliva samples were collected at baseline (day 0), day 14, and day 28 after taking probiotic lozenges to measure cytokine levels (IL-6) using ELISA assays. Gingival health was assessed using the Gingival Index. Results: The period at 28 days for Gingival Index (GI) recorded the lowest mean±SD, at 0.517 ±0.23, closely followed by the highest record at the baseline period (day 0) with a mean±SD of 1.51 ±0.18. In contrast, the period at 14 days showed mean±SD, at 0.94 ±0.26. Statistical analysis indicated a significant differences among these periods (p-value < 0.05).